Pausania e Roma (Nota di lettura a VIII 27, 1) - Moggi, Mauro (Gerión. Revista de Historia Antigua, 2002)
The paper suggests new argumets suppoting the integration of έπί τήζ between the words συμφοράυ and άρχής in Paus. VIII 27, 1. Therefore, the passage will lose the strong and explicit anti-roman charge it will have when we identify the συμφορά with Romans άρχή Still resisting are, however, the general reasons allowing us to evognize, in other statements and attitudes clearly represented in Periegesis, that Pausanias had a unpeaceful acceptance of Greeks´ subjection, and conflictual feelings about the new rulers.